(untitled) (Research, Society and Development, 2025)
The consumption of high-fat diets is a global problem. The use of micronutrients, such as calcium and vitamin D, has positive effects on glucose metabolism during pregnancy, reproductive performance, and embryofetal development. This study aims to evaluate the effects of a mixture of micronutrients on glucose metabolism and perinatal outcomes in rats exposed to a high-fat diet (HFD). The female rats received a standard diet (SD) or high-fat diet (HFD) from weaning to the end of pregnancy. The pregnant rats were treated with the micronutrient mixture (Mix) only during pregnancy, and were distributed into 4 groups: SD, SD+Mix, HFD, and HFD+Mix. At the end of pregnancy, the rats were euthanized for collection of maternal adipose tissue, maternal and fetal blood samples, and placental samples. The HFD dams presented a higher number of fetuses with low weight at birth compared to the SD groups. Fetuses from SD+Mix and HFD+Mix had higher serum concentrations of vitamin D compared to the control respective groups. The HFD+mix group had higher maternal serum concentrations of vitamin D and increased rate of fetal viability, lower maternal visceral fat weight and lower percentage of embryonic deaths compared to the HFD group. Thus, the Mix treatment causes benefits to mothers and offspring exposed to HFD intake because of improved maternal glycemia, lower adiposity index, increased serum vitamin D, and embryofetal viability. This study shows the importance of prioritizing a healthy diet to achieve maternal physical well-being and enable the healthy development of offspring.